Proceedings of the 5th International Conference on Education and Technology (ICET 2019) 2019
DOI: 10.2991/icet-19.2019.181
|View full text |Cite
|
Sign up to set email alerts
|

Office Management of Educational Institutions: Theories and Applications

Abstract: All activities carried out by the organization require a place in supporting employee activities. The office is a place to support employees in carrying out their work in an organization. Therefore, efforts to carry out office activities need to be handled professionally, in the sense that the implementation of office activities requires leaders and staff who understand their duties, are enthusiastic in pursuing achievements, and an employee is expected to devote his attention seriously, and try to be able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This NeCard game, practically invites principals to think rationally, systematically, and comprehensively in seeing a problem at school. With his leadership behavior, the principal is expected to lead his teachers, staff, and students to achieve the school's vision, mission, and goals [44][45][46]. Through this NeCard game, principals are directly trained to think about solving school problems and think about what schools can do in the future [13,[47][48][49][50], so that schools can improve the quality of their teaching continuously.…”
Section: Resultsmentioning
confidence: 99%
“…This NeCard game, practically invites principals to think rationally, systematically, and comprehensively in seeing a problem at school. With his leadership behavior, the principal is expected to lead his teachers, staff, and students to achieve the school's vision, mission, and goals [44][45][46]. Through this NeCard game, principals are directly trained to think about solving school problems and think about what schools can do in the future [13,[47][48][49][50], so that schools can improve the quality of their teaching continuously.…”
Section: Resultsmentioning
confidence: 99%
“…The cooperation in question is in the form of education management and activities to improve the quality of education, expand partnership networks, and organize educational units or study programs of international standard or based on local excellence [39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…This study also suggests the importance of collective participation and coherence of activities in the supervision of learning, guiding professional communication activities among teachers to support changing ways of making the learning process more effective. Green and Allen's [62] found that the quality of teacher professional development (learning supervision) designed with professional learning elements contributed to higher student achievement [39], [63]- [67].…”
Section: Discussionmentioning
confidence: 99%